Effect of the nutrient solution in the microbial production of citric acid from sugarcane bagasse and vinasse. (May 2019) - Campanhol, B.S.; Silveira, G.C.; Castro, M.C.; Ceccato-Antonini, S.R.; Bastos, R.G.
Abstract: The process known as "solid-state cultivation" (SSC) refers to microbial growth on solid supports under limited water conditions. Citric acid is a bioproduct with several industrial applications, and its production is traditionally microbial. The present work evaluated the production of citric acid by microbial consortium of Aspergillus niger and Trichoderma reesei in sugarcane bagasse with vinasse and ethanol as inducer of the metabolic production of this organic acid. The results indicate that the highest yields of glucose in citric acid, productivity and specific production rate for the conditions having vinasse and vinasse/ethanol as nutrient solution. In addition, the kinetic parameters for the citric acid and glucose profiles indicate that only vinasse as a nutrient solution, has a maximum citric acid concentration of 734 mg L −1 in 48 h. Highlights: Unconventional solid-state cultivation (SSC) by fungal consortium from agro industrial byproducts. Using vinasse, sugarcane processing wastewater, as nutrient solution for citric acid production by SSC. Effect of ethanol as inducer of microbial citric acid production.